Assesing needs and scopes of upgrading urban squatters in Bangladesh - Roy, Gouri S.; Abduallah, A.Q.M (BRAC University, 2010)
In almost all urban areas of developing countries squatter growth is a common phenomenon, characterized by filthy, dense, unhygienic and poorly-serviced human settlement, which can pose paramount threat to the discipline and health of city life. If proper measures are not taken the squatters dwellers might generate serious political agitation for improved housing. A number of upgrading projects so far have been taken for squatters to improve living standard and secure tenure throughout the developing world. Lots of difficulties have been faced by both dwellers and project implementing authorities in this regard, specially in devising the optimum utilization of scares resources. Few experiments have been made following the UN-Habitat specifications in countries like Brazil, Sub-Saharan Africa and in other Least Developed Countries (LDC). Along with all technical factors that can be measured in quantitative form social and motivational factors are getting priority day by day. Participatory approach is now considered more beneficial compared to authoritative decisions in upgrading schemes. In this context information on dwellers’ root of origin, their traditional history, desires, views, ideas, choice of priority can unfold a new horizon of understanding. Upgrading process that is based on dwellers choices and participation will obviously work better as this will enhance their motivation. In this paper application of information on dwellers background history is suggested and pointed a different approach to upgrade squatters into sustainable settlements in urban context of Bangladesh.